Total Joint Arthroplasty in HIV-Positive Patients in Malawi: Outcomes from the National Arthroplasty Registry of the Malawi Orthopaedic Association. Issue 4 (October 2021) - Graham, Simon Matthew; Render, Luke; Moffat, Chipiliro; Lubega, Nicholas; Mkandawire, Nyengo; Young, Sven; Harrison, William J.
Abstract : Background: In this observational study, we describe the medium-term outcomes of total joint arthroplasty (TJA) in human immunodeficiency virus (HIV)-positive patients in Malawi, a low-income country. With a high prevalence of HIV and increasing arthroplasty rates in low and middle-income countries, understanding the outcomes of TJA in this unique cohort of patients is essential to ensure that surgical practice is evidence-based. Methods: Data for all HIV-positive patients who had TJA from January 2005 to March 2020 were extracted from the National Arthroplasty Registry of the Malawi Orthopaedic Association (NARMOA). From January 2005 to March 2020, a total of 102 total hip arthroplasties (THAs) and 20 total knee arthroplasties (TKAs) were performed in 97 patients who were HIV-positive and without hemophilia or a history of intravenous drug use. The mean length of follow-up was 4 years and 3 months (range, 6 weeks to 15 years) in the THA group and 4 years and 9 months (range, 6 weeks to 12 years) in the TKA group. The mean patient age was 50 years (range, 21 to 76 years) and 64 years (range, 48 to 76 years) at the time of THA and TKA, respectively. Results: The primary indication for THA was osteonecrosis (66 hips). In the THA group, the mean preoperative Oxford Hip Score and Harris hip score were 14.0 (range, 2 to 33) and 29.4 (range, 1 to 64), respectively, and improved to 46.6 (range, 23 to 48) and 85.0 (range, 28 to 91) postoperatively. The primary indication for TKA was osteoarthritis (19 knees). The mean preoperative Oxford Knee Score was 14.9 (range, 6 to 31) and increased to 46.8 (range, 40 to 48) postoperatively. In patients who underwent THA, there was 1 deep infection (1 of 102 procedures), and 6 patients developed aseptic loosening (6 of 102). There was 1 postoperative superficial infection following TKA (1 of 20 procedures), and 1 patient developed aseptic loosening (1 of 20). Postoperative 6-week mortality among all patients was zero. Conclusions: To our knowledge this is the largest medium-term follow-up of HIV-positive patients, without hemophilia or a history of intravenous drug use, who have had TJA in a low-income country. This study demonstrated good medium-term results among HIV-positive patients undergoing TJA, low complication rates, and improvements in patient-reported outcome measures. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.